Settlement Adaptation Model for Flood Disaster Mitigation in Salomenraleng Village Wajo Regency - Naidah Naing; Asdar Djamereng (Center for Scientific Publication, 2023)
The background of this research is that there is a flood disaster that hits residential areas in Salomenraleng Village every year with flood inundation for months. This can lead to a decline in the quality of life, housing and public facilities because they cannot function properly and can threaten the safety of the community. However, decades of experience dealing with floods have created a formidable adaptation process for this community. The purpose of this study was to find an adaptation model for living that can mitigate flood disasters in the village of Salomenraleng in order to improve the safety and security of living. The method used in this research is descriptive-spatial using morphological, behavioral and architectural approaches. The results of this study are to find architectural adaptations by creating space in the space in the form of ladda', morphological adaptation is to change the height of the house/other facilities and create Alleteng awo' (floating street) in the face of flood disasters. Novelty This research is the discovery of architectural engineering models in flood disaster mitigation.